I'm told that (R = v/f*L) is the same thing as (L = v/f*r) but I can't seem to get there algebraiclaly. If anyone can show me all the steps I'd be very appreciative.
I'm told that (R = v/f*L) is the same thing as (L = v/f*r) but I can't seem to get there algebraiclaly. If anyone can show me all the steps I'd be very appreciative.
Use brackets where they're needed please. Is it $\displaystyle \displaystyle \begin{align*} R = \frac{v}{f\cdot L} \end{align*}$ or $\displaystyle \displaystyle \begin{align*} R = \frac{v}{f}\cdot L \end{align*}$? What you wrote implies the latter...